Rendering the Popular as "Tradition": The Music of Virgilio "Pirot" Petcheller and the Panay Bukidnon Banda Music Practice in Panay Island, Philippines - Taton, Jose Jr Rabara (Malaysian Journal of Music, 2020)
In recent years, the popular music of Virgilio “Pirot” Petcheller had been included in the banda (ensemble) musical repertoire, practice and identity of several indigenous cultural communities in Panay Island located in Western Visayas, Philippines. Pirot’s music, particularly renderings of folk music genres, such as harana (serenade) and komposo (ballad), had been in mainstream broadcast media and were widely produced by the recording industry in the 1970s. Because of the parallels between his music and West Visayan folk practice, folk musicians categorically ascribe and recognise his music as dinuma-an (tradition and traditional) to refer to a standard folk canon with an associated pastoral imagery. Later, Pirot’s music had become emblematic of a regional folk, cultural and/or ethnic identity. This paper investigates the problematic fluidity of boundaries between traditional and popular music categories and its implications in the construction of identity in the Western Visayan context. I examine, on the one hand, how the popular music of Pirot are rendered as “tradition” notably through a discussion on musical aesthetics, lyricism and imagery and the complex socio-cultural and historical context musicians occupy. On the other hand, this paper also proffers a discussion on how this rendering or “traditionalisation” plays a role in the construction of identity among the Panay Bukidnon banda musicians. On this, I recognise the central role of cultural praxis and individual agency in the process and argue that musical categories, particularly the notion of ‘tradition’ and ‘traditional’, are self-conscious devices defined by, and are constitutive of practice.